Back Cover: Cover Image, Volume 21, Issue 5. Issue 5 (29th August 2018) - Bathelt, Joe; Gathercole, Susan E; Butterfield, Sally; ,
Abstract : The cover image, by Joe Bathelt et al., is based on the Paper Children's academic attainment is linked to the global organization of the white matter connectome, DOI: 10.1111/desc.12662 .